Quantitative in situ SEM high cycle fatigue: The critical role of oxygen on nanoscale-void-controlled nucleation and propagation of small cracks in Ni microbeams - Barrios, Alejandro; Gupta, Saurabh; Castelluccio, Gustavo M.; Pierron, Olivier N. (Cranfield University, 2018)
This Letter presents a quantitative in situ scanning electron microscope (SEM) nanoscale high and very high cycle fatigue (HCF/VHCF) investigation of Ni microbeams under bending, using a MEMS microresonator as an integrated testing machine. The novel technique highlights ultraslow fatigue crack growth (average values down to ∼10–14 m/cycle) that has heretofore not been reported and that indicates a discontinuous process; it also reveals strong environmental effects on fatigue lives that are 3 orders of magnitude longer in a vacuum than in air. This ultraslow fatigue regime does not follow the well documented fatigue mechanisms that rely on the common crack tip stress intensification, mediated by dislocation emission and associated with much larger crack growth rates. Instead, our study reveals fatigue nucleation and propagation mechanisms that mainly result from room temperature void formation based on vacancy condensation processes that are strongly affected by oxygen. This study therefore shows significant size effects governing the bending high/very high cycle fatigue behavior of metals at the micro- and nanoscales, whereby the stress concentration effect at the tip of a growing small fatigue crack is assumed to be greatly reduced by the effect of the bending-induced extreme stress gradients, which prevents any significant cyclic crack tip opening displacement. In this scenario, ultraslow processes relying on vacancy formation at the subsurface or in the vicinity of a crack tip and subsequent condensation into voids become the dominant fatigue mechanisms.
Keywords: environmental effects; high cycle fatigue; Nanomechanics; quantitative in situ SEM; small cracks; voids